Konsep Perencanaan Pendidikan Islam Tuan Guru Haji Muhammad Shaleh Hambali Bengkel: Studi Kitab Ta‘lim Al-Shibyan Bi Ghayati Al-Bayan - Lalu Agus Murzaki; Fitrah Sugiarto (UIN Mataram, 2020)
This article focuses on exploring the contents of the book Ta'lim al-Sibyan Bighayat al-Bayan by Tuan Guru Haji Muhammad Shaleh Hambali Bengkel on the concept of educational planning. This article also aims to find a model for the concept of planning Islamic education, with the hope that it can be useful for management and management of Islamic education. This research is a study of the thoughts of figures using library theory or library research, using a historical approach, with data collection methods in accordance with the type of research, namely library research. The data analysis in this study uses the interpretation method (text interpretation), it can also be translated using the text of the book as a research field, in this case the book Ta'lim al Sibyan Bighayati al Bayan which specifically shows the concept of educational planning. From this research, it has been found that 1) the concept of teaching staff planning, curriculum planning and financial planning; The contemporary context that planning is integrated with national ideals, namely building intellectual intelligence and moral intelligence through a planned curriculum and realistic funding.